(3GdeSCdI GdMcejIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hGdMeO ef fYeg CeG HYO abO SCdfi HYV ef fJefi Gf GPcQ dg QSGdI eTJedI Ydi Ydi GdJhMjO Ydi GdhLg GdPi jLH Gf jYJbO ai Gddg hUaGJg s
(3BNQgG (B:s
(3aGPG bO KHJ Gf GdNjQ ebUhO HGdbUO GdChd hGdMeO ddg hGgH GdYbd s
(3Vef eLehY , JQJjHgG (B: (3GdNGeS hGdKdGKhfs
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs